A metastable phase of shocked bulk single crystal copper: an atomistic simulation study - Anupam Neogi; Nilanjan Mitra (Scientific Reports, 2017)
Abstract Structural phase transformation in bulk single crystal Cu in different orientation under shock loading of different intensities has been investigated in this article. Atomistic simulations, such as, classical molecular dynamics using embedded atom method (EAM) interatomic potential and ab-initio based molecular dynamics simulations, have been carried out to demonstrate FCC-to-BCT phase transformation under shock loading of 〈100〉 oriented bulk single crystal copper. Simulated x-ray diffraction patterns have been utilized to confirm the structural phase transformation before shock-induced melting in Cu(100).